The challenge of the Molecular Tumor Board empowerment in clinical oncology practice: A Position Paper on behalf of the AIOM- SIAPEC/IAP-SIBioC-SIC-SIF-SIGU-SIRM Italian Scientific Societies. (January 2022) - Russo, Antonio; Incorvaia, Lorena; Capoluongo, Ettore; Tagliaferri, Pierosandro; Galvano, Antonio; Del Re, Marzia; Malapelle, Umberto; Chiari, Rita; Conte, Pierfranco; Danesi, Romano; Fassan, Matteo; Ferrara, Roberto; et al.
Graphical abstract: Highlights: Genetics/genomics offer new opportunities for personalized treatment in oncology. The model of mutational oncology is extremely complex. Universal access, homogeneity and sustainability should be warranted. The Molecular Tumor Board empowerment in clinical oncology practice is a challenge. Abstract: The development of innovative technologies and the advances in the genetics and genomics, have offered new opportunities for personalized treatment in oncology. Although the selection of the patient based on the molecular characteristics of the neoplasm has the potential to revolutionize the therapeutic scenario of oncology, this approach is extremely challenging. The access, homogeneity, and economic sustainability of the required genomic tests should be warranted in the clinical practice, as well as the specific scientific and clinical expertise for the choice of medical therapies. All these elements make essential the collaboration of different specialists within the Molecular Tumor Boards (MTBs). In this position paper, based on experts' opinion, the AIOM-SIAPEC/IAP-SIBioC-SIC-SIF-SIGU-SIRM Italian Scientific Societies critically discuss the available molecular profiling technologies, the proposed criteria for the selection of patients candidate for evaluation by the MTB, the criteria for the selection and analysis of biological samples, and the regulatory and pharmaco-economic issues.